China-UK partnership for global health: practices and implications of the Global Health Support Programme 2012-2019 - Xiaohua Wang; Peilong Liu; Tongwu Xu; Yan Chen; Yang Yu; Xun Chen; Jingyi Chen; Zhaoyang Zhang (BMC, 2020)
Abstract Background Over the past few decades, a series of major challenges to global health have successively emerged, which call for China's deeper engagement in global health governance. In this context, the China-UK Global Health Support Programme (GHSP) was launched in 2012 with about 12 million pounds funded by the United Kingdom. Objectives The GHSP was expected to explore a new type of China-UK partnership to strengthen the cooperation in global health, and enhance China's capacity to engage in global health governance and provide effective development assistance in health (DAH), in order to jointly improve global health outcomes. Programme design and implementation The GHSP was programmed to support capacity building activities in Chinese experience distillation, DAH, global health governance and pilot partnership at national and institutional levels between October 2012 and March 2019. These activities were assigned to different project implementing agencies (PIAs) and their project cooperative agencies (PCAs) or pilot areas, and were then implemented under the guidance and management by the strategic oversight committee and the project management office of GHSP respectively. Main achievements At the national level, the GHSP held five rounds of China-UK high-level dialogues, conducted studies on China Global Health Strategies to provide robust evidence for developing and issuing relevant national policies, and supported the establishment of the China Global Health Network. At the institutional level, the GHSP funded a series of activities in research, training, international exchange and pilots etc., produced a large number of high-quality research outputs and policy briefings, cultivated a group of PIAs and individual researchers, facilitated the partnership building between the PIAs and PCAs, enhanced the practical ability of Chinese institutions to conduct overseas DAH, and improved the health service delivery and outcomes in pilot areas of three Asian and African countries. Policy implications In the GHSP, China and UK have established a good model for North-South Cooperation and the programme facilitated the 2030 Agenda for Sustainable Development by building a new type of bilateral partnership and carrying out triangular cooperation practices. This model has demonstrated huge potential for cooperation through partnership and can also be referred to by other countries to develop bilateral partnerships.